(1202) planning in Hungary التخطيط في المجر - morva, tamas (the institute of national planning, 2018)
the postwar result of the hungarian economy are closely linked to the development of national planning. the first three-year plan guided the reconstruction of the economy it repaired war damage and regained the prewar level of production, while exceeding former living standards of the population through a new distribution of the national income.